ANALISIS PENALARAN MATEMATIS SISWA DENGAN GAYA KOGNITIF IMPULSIF DITINJAU DARI GENDER - SITI NURIYATIN (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2022)
This study aims to analyze the mathematical reasoning ability of students with impulsive cognitive style in terms of gender. Qualitative descriptive is this type of research. The research subjects were two students, one female student and one male student. This research was conducted in class VII SMP. The instruments in this research are MFFT, reasoning tests, and interviews. The results of this study indicate that female subjects can perform mathematical manipulations, while male subjects can perform mathematical manipulations and check the validity of an argument.